Characterizing online political participation in social media (Facebook,Twitter, Tiktok, & YouTube) of registered voters in Western Visayas - Araneta, Klaire Marie J.
The shift in the media landscape established the path for new media to be used as a political campaign tool. In the 2022 Philippine election, new media exert significant influence over voter turnout. The purpose of this study is to determine the onlne political participation of Western Visays registered voters on various social media platforms, primary Facebook, Twitter, TikTok, and You Tube. While some people believe that internal factors have minimal impact on their online behavior, disparities in voter's socio-demographic profiles, social media choices, and level of social media usage influence their online behavior. The methodology used in the study is a quantitative approach with a descriptive research design. The study focused on five main areas: (1) voter's socio-demographic profiles; (2) frequently utilized social media; (3) online political involvement based on digital media; (4)online political activities based on other variables; and (5) notable variations in online participation. The findings revealed that socio-demographic factors had a significant impact on voters' political engagement online. By investigating and analyzing the differences in their social media choice and usage, the researchers were able to characterize their online involvement on different social media channels. For instance, most Facebook users are categorized into two groups: Joiners and Searchers. Likewise, the majority of Twitter users are Creators, Conversationalists, Joiners, and Searchers. TikTok, the site with the least online political participation, classify its users as Joiners and Searches. Finally, those who are classed as Spectators and Searchers frequently use You Tube in accessing, engaging, and participating in online political activities. Certainly, social media today wields significantly more power than ever in influencing how voters receive and disseminate political information online.